A Sasanian coin of Khosrow I and an Abbasid coin of Al-Manṣur from the Areni-1 Cave, Armenia - Zohrabyan, Armine; Gasparyan, Boris; Dan, Roberto (ARAMAZD: Armenian Journal of Near Eastern Studies, 2018)
This article concerns the presentation of two unpublished coins discovered in the cave of Areni-1 (the Birds’ Cave). The Areni-1 cave is a particularly important site (Figure 1) mainly thanks to its very well preserved Late Chalcolithic sequence (4.300–3.400 Cal BC). In addition, important medieval (4th–18th centuries AD) occupations were found. The coins were discovered in July 2010, during the fifth season of excavations, inside the cave in Trench 2A in Gallery no. 1, in the lower level of the Late Medieval pit area (Figure 2). The coins were probably part of a hoard disturbed by excavation activities in the Late Medieval period. One coin dates to the Sasanian period and may be attributed to Khosrow I Anōšīravān. The beginning of the Sasanian domination of the Armenian highlands started in 428 AD with the investiture of Veh Mihr Shapur (428-442 AD) as marzbān by Bahrām V Gōr (406-438 AD). These years correspond to the earlier phase of the Early Medieval period in the regional chronology, a period of important socio-economic and cultural changes for Armenia. The second coin is of the Abbasid Caliph Abū Jaʿfar Abd Allāh ibn Muḥammad al-Manṣūr. In this period Armenia, then called Arminiya or the Emirate of Armenia, was part of the Abbasid Caliphate. During this time, al-Manṣūr revoked the privileges and subsidies of the local rulers (naxarar) and imposed harsh taxation. This situation led to a major rebellion in 774 AD. The revolt was suppressed by the Battle of Bagrevand in 25 April 775 AD.